2023
DOI: 10.3390/cancers15041279
|View full text |Cite
|
Sign up to set email alerts
|

P21 Overexpression Promotes Cell Death and Induces Senescence in Human Glioblastoma

Abstract: High-grade gliomas are the most common and aggressive adult primary brain tumors with a median survival of only 12–15 months. Current standard therapy consists of maximal safe surgical resection followed by DNA-damaging agents, such as irradiation and chemotherapy that can delay but not prevent inevitable recurrence. Some have interpreted glioma recurrence as evidence of glioma stem cells which persist in a relatively quiescent state after irradiation and chemotherapy, before the ultimate cell cycle re-entry a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Conversely, elimination of the SA-β-gal-positive population by navitoclax enriched for cells expressing normal p21 levels. Elevated levels of p21 itself can induce senescence, as shown in several cell lines, including GBM (50,51). Interestingly, this induction can be prevented by restricting cellular size growth using mTOR inhibitors (50).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, elimination of the SA-β-gal-positive population by navitoclax enriched for cells expressing normal p21 levels. Elevated levels of p21 itself can induce senescence, as shown in several cell lines, including GBM (50,51). Interestingly, this induction can be prevented by restricting cellular size growth using mTOR inhibitors (50).…”
Section: Discussionmentioning
confidence: 99%
“…In response to p53 transcription factor activity, p21 induction may result in tumor growth arrest through the inhibition of cyclin-dependent kinase complexes, proliferation cell nuclear antigen, transcription factors and coactivators ( 25 ). The overexpression of p21 has been demonstrated to promote cell death and induce senescence in human glioblastoma ( 27 ). Consistent with this, the present study has confirmed that p21-knockdown promotes the proliferation of GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Te detection of apoptosis-related proteins using a human apoptotic antibody kit showed that the expression of the apoptosis-inhibiting protein survivin and proliferationinhibiting protein p21 were diferent between A2ML1 overexpression ESCC cells and the control group. p21, a well-established cyclin-dependent kinase inhibitor, plays an important role in controlling cell-cycle progression [20,21]. Moreover, p21 is mainly associated with p53 during cell-cycle arrest.…”
Section: Discussionmentioning
confidence: 99%